Misquoting Jesus The story behind who changed the Bible and why - Ehrman, Bart D. frey50 (New York HarperSanFranciscoiety, 2005)
When Biblical scholar Ehrman first began to study the texts of the Bible in their original languages, he was startled to discover the multitude of mistakes & intentional alterations that had been made
Keywords: Bible.-pN.T.-xCriticism, Textural; Bible.-pN.T.-xCriticism, Textural-xHistory.; Bible.-pN.T.-xManuscripts.